THE EFFECT OF BRAND IMAGE AND PRICE PERCEPTION ON THE PURCHASE DECISION OF ASUS BRAND LAPTOPS IN RISKY MEDIA COMPUTER STORE - Redina Restu Hapsari; Siti Aminah (Institute of Computer Science (IOCS), 2021)
The purpose of this study was to determine the effect of brand image and price perception on purchasing decisions for ASUS brand laptops at the Risky Media Computer store. Respondents in this study were Risky Media Computer shop consumers who had bought an ASUS brand laptop. The number of respondents as many as 100 people. sampling using the methodaccidental sampling. Collecting data using a questionnaire. The data analysis technique in this study used Partial Least Square (PLS). Based on data analysis and discussion results, it can be seen that: 1)Brand image (X1) has a positive effect on purchasing decisions (Y) is acceptable, with path coefficients of 0.324084, and a T-statistic value of 3.132602 > 1.96 (from the table value Zα = 0.05). 2) Price perception (X2) has a positive effect on purchasing decisions (Y) is acceptable, with path coefficients of 0.522840, and a T-statistic value of 6.144804 > 1.96 (from the table value Zα = 0.05). The conclusion is that brand image and price perception contribute to Asus laptop purchasing decisions.